Penerapan Arsitektur Bioklimatik Pada Science Technology Park Universitas Riau - Fatmadhita Arumsari; Yohannes Firzal; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Advance Technologies exist everywhere these day. They can accommodate a number of informative media about science and technology that are accessable for everyone, such as students and public. In this paper, the Science Technology Park is developed in University of Riau as a facility by using Bioclimatic Architecture approach in responding to the problem of energy efficiency and environment. Application of Bioclimatic Architecture becomes a medium for learn about buildings how they respons to local climate. From this, the concept of Hidden Sciemce is conveyed as visualization of teaching and learning facilities that is not visible directly from outside the site. Principles of Bioclimatic Architecture such as landscape, transition, opening, and orientation is applied to the concept of Hidden Science.Keywords: Techno & Science Park, Bioclimatic Architecture